Glaucocalyxin A Inhibits the Malignancies of Gastric Cancer Cells by Downregulating MDM2 and RNF6 via MiR-3658 and the SMG1-UPF mRNA Decay Pathway - Liu, Yanqi; Chen, Ping; Qi, Daqing; Chen, Linhui (Frontiers in Oncology, 2022)
Gastric cancer (GC) ranks as the most common gastrointestinal cancer and is among the leading causes of cancer death worldwide. Glaucocalyxin A (GLA), an entkauranoid diterpene isolated from Rab-dosia japonica var., possesses various bioactivities. To date, the data on the effect of GLA on GC are still minimal, and the molecular mechanisms remain largely unknown. Herein, we found that GLA could significantly inhibit the proliferation, cell adhesion, and invasion of HGT-1, SNU-1, SNU-6, and NCI-N87 GC cells in a dose-dependent manner. GLA enhanced the apoptosis of the GC cells as evidenced by the increased caspase-3 activity and the elevated levels of cleaved caspase-3 and cleaved PARP in GC cells in the presence of GLA. We then showed that the downregulation of Murine Double Minute Clone 2 (MDM2) and Ring Finger Protein 6 (RNF6) by GLA was implicated in the GLA-induced inhibition of the GC cells. Furthermore, MDM2 and RNF6 were identified as the targets of miR-3658 that was downregulated in the GC cells and upregulated by GLA. Moreover, it was shown that miR-3658 was hypermethylated in the GC cells, and GLA could rescue the expression of miR-3658 via demethylation by abrogating EZH2-mediated epigenetic silencing. In addition to the miR-3658-MDM2/RNF6 regulatory axis, activation of the SMG1-UPF mRNA decay pathway contributed to the downregulation of MDM2 and RNF6 by GLA in the GC cells. The inhibitory effect of GLA on gastric cancer and the expression of MDM2 and RNF6 was also validated in in vivo study. Our findings suggest that has the therapeutic potential for GC by downregulating oncogenes via posttranscriptional regulation.